2016
DOI: 10.1016/j.physbeh.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and molecular effects of restraint stress on formalin-induced pain-like behavior in male and female mice

Abstract: The evolutionary advantages to the suppression of pain during a stressful event (stress-induced analgesia (SIA)) are obvious, yet the reasoning behind sex-differences in the expression of this pain reduction are not. The different ways in which males and females integrate physiological stress responses and descending pain inhibition are unclear. A potential supraspinal modulator of stress-induced analgesia is the central nucleus of the amygdala (CeA). This limbic brain region is involved in both the processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 37 publications
0
9
1
1
Order By: Relevance
“…Bilateral injections of retrograde tracer into the medial prefrontal cortex (mPFC) combined with the immunohistochemical detection of Fos family proteins revealed that amygdala neurons projecting to the mPFC were not immunoreactive for either cFos or FosB/∆FosB suggesting that this speci c pathway is not activated by either acute restraint, CCI, or a combination of these stimuli. Our experiments were carried out exclusively in male rats, we are aware however that there is evidence for sex differences in the role of the amygdala in mediating changes in pain sensitivity as a result of chronic stress (Long et al, 2016), whether our ndings of the effects of neuropathic injury on amygdala responses to acute stressors is also seen in female rats will be important to determine as there are many more females with chronic pain than males (Mogil, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral injections of retrograde tracer into the medial prefrontal cortex (mPFC) combined with the immunohistochemical detection of Fos family proteins revealed that amygdala neurons projecting to the mPFC were not immunoreactive for either cFos or FosB/∆FosB suggesting that this speci c pathway is not activated by either acute restraint, CCI, or a combination of these stimuli. Our experiments were carried out exclusively in male rats, we are aware however that there is evidence for sex differences in the role of the amygdala in mediating changes in pain sensitivity as a result of chronic stress (Long et al, 2016), whether our ndings of the effects of neuropathic injury on amygdala responses to acute stressors is also seen in female rats will be important to determine as there are many more females with chronic pain than males (Mogil, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [13], spontaneous behaviors following intraplantar formalin injection were measured. Mice were firstly acclimatized for 60 min in an individual Plexiglas cage placed atop a glass surface and then were videotaped following intradermal formalin injection and analyzed for nociceptive behaviors (defined as licking, lifting, and flinching of the injected paw, sum of licking/biting times were counted) in five min bins for 60 min following formalin injection.…”
Section: Methodsmentioning
confidence: 99%
“…The high-profile observation that κ-opioid receptor agonists produce analgesia in men but not women 110 -which engendered great interest in the subfield at its inception -was not replicated in a subsequent study using three experimental pain models 111 . However, two further examples of male-specific endogenous analgesia systems have recently been described, including a naloxone-sensitive system that suppresses orofacial pain in male mice 112 and a restraint stress inhibition of formalin pain in male mice involving the central amygdala 113 . Chronic pain has been shown to produce long-lasting changes in neuroanatomy 114 ; recent reports suggest that some of these changes might be dependent on sex.…”
Section: Sex Differences In the Neural Mediation Of Painmentioning
confidence: 99%